Postoperative ERAS Interventions Have the Greatest Impact on Optimal Recovery: Experience With Implementation of ERAS Across Multiple Hospitals. Issue 6 (June 2018) - Aarts, Mary-Anne; Rotstein, Ori D.; Pearsall, Emily A.; Victor, J. Charles; Okrainec, Allan; McKenzie, Marg; McCluskey, Stuart A.; Conn, Lesley Gotlib; McLeod, Robin S.
Abstract : Background: Enhanced recovery after surgery (ERAS) programs incorporate evidence-based practices to minimize perioperative stress, gut dysfunction, and promote early recovery. However, it is unknown which components have the greatest impact. Objective: This study aims to determine which components of ERAS programs have the largest impact on recovery for patients undergoing colorectal surgery. Methods: An iERAS program was implemented in 15 academic hospitals. Data were collected prospectively. Patients were considered compliant if >75% of the preoperative, intraoperative, and postoperative predefined interventions were adhered to. Optimal recovery was defined as discharge within 5 days of surgery with no major complications, no readmission to hospital, and no mortality. Multivariable analysis was used to model the impact of compliance and technique on optimal recovery. Results: Overall, 2876 patients were enrolled. Colon resections were performed in 64.7% of patients and 52.9% had a laparoscopic procedure. Only 20.1% of patients were compliant with all phases of the pathway. The poorest compliance rate was for postoperative interventions (40.3%) which was independently associated with an increase in optimal recovery (RR = 2.12, 95% CI 1.81–2.47). Compliance with ERAS interventions remained associated with improved outcomes whether surgery was performed laparoscopically (RR = 1.55, 95% CI 1.23–1.96) or open (RR = 2.29, 95% CI 1.68–3.13). However, the impact of ERAS compliance was significantly greater in the open group ( P < 0.001). Conclusions: Postoperative compliance is the most difficult to achieve but is most strongly associated with optimal recovery. Although our data support that ERAS has more effect in patients undergoing open surgery, it also showed a significant impact on patients treated with a laparoscopic approach.